O fracasso escolar no discurso do professor - Piccirilli, Manoela de Souza Silva (2014)
School failure has been constant focus of studies of several natures that search for different reasons for its occurrence. This dissertation does not intend to develop one more hypothesis as to what school failure may be, but to analyze its meanings in the discourse of some elementary education teachers. This is a qualitative study conducted using Discourse Analysis theory and method, based on Michel Pêcheux. The procedure for data collection took place in a room for discussions among elementary education teachers and researchers. Two of the meetings were chosen to look for discourse formations that would characterize this group of teachers as subjects. Discourse data were collected on a voice recorder and then transcribed in regular orthography. Fragments of the corpus were extracted for analysis. During the first meeting, a search for homogeneity in detriment of students singularities was identified; there was a process of production of meanings based on school ideals that are dominated by a capitalist educational policy that, in treating students as equals and not reflecting on their singularities, contributes to school failure. On the second meeting there was discourse functioning that admitted the presence of the child as a subject who has needs and desires beyond those imposed by a school ideal, thus producing new meanings other than school failure. It may be considered that the meanings of school failure in these teachers discourse emerge as the effect of an educational logic regulated by a capitalist discourse that, in trying to control the child s knowledge, lets something interpreted as school failure slide. However, when this discourse is suspended, school failure may gain new meanings, thus contributing to the process of literacy